The Effect of Instructional Adaptations Training within Inclusive Practices on Classroom Teachers' Opinions about the Importance of Instructional Adaptations - Emine Sema Batu; Emrah Bilgiç (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: Adaptations must be made by teachers for students with Special Educational Needs (SEN) to take part in the successful inclusion practices (SIP) process and to ensure effective teaching. However, teachers struggle to make adaptations for various reasons during the instructional process, either finding it difficult to make adequate adaptations or being unable to make any adaptations at all. For this reason, there is a problem with the realization of the SIP, and the educational needs of the students with SEN cannot be met properly. The study aims to examine the effect of an information package application (IPA) prepared on instructional adaptations (IA) for classroom teachers on teachers' opinions on the importance of IA.Method: In the study, mixed method and “multi-stage mixed design” were used as the research design. The research consists of five stages: i. Determination of opinion (requirement) before SIP, ii. SIP preparation and implementation, iii. determination of SIP effectiveness, iv. determination of social validity related to SIP, and v. Stage: Monitoring phase respectively. The participants of the study are primary school class teachers from Hendek district of Sakarya province, who have students with SEN in their class (60 [Experimental group: n = 30, control group: n = 30] in the quantitative dimension, 31 teachers in the qualitative dimension). The qualitative data of the research was obtained through focus group interviews (FGI). Quantitative dimension data of the research was obtained by using the Scale of Instructional Adaptations for Inclusion (SIMI); social validity data were obtained by using the Social Validity Form; and the data containing personal information was obtained by using the demographic information form.Findings: The findings of the research indicate that the implementation of the IPA has positively changed teachers' opinions regarding the importance of individualized education. “Social validity determination” findings of the study show that teachers find the IPA performed useful and functional.Discussion: The research findings have been discussed within the framework of the relevant literature, and recommendations and limitations related to the study have been stated.